Improving Students' Understanding of the Pillars of Islam Through the Role Play Method at SD Negeri No. 105408 Suka Makmur - Hayati, Junainah; Rahim, Abdur (DARUSSALAM: Scientific Journal of Islamic Education, 2024)
This classroom action research was conducted to improve fourth-grade students’ understanding of the Pillars of Islam at SD Negeri No. 105408 Suka Makmur through the application of the role play method. The study was initiated based on initial observations indicating that students struggled to grasp the material due to monotonous teaching methods that lacked active student engagement. The research involved 30 students and was carried out in two cycles, each consisting of planning, action, observation, and reflection stages. Data collection instruments included pretests and posttests to assess students’ understanding, observation sheets to monitor student participation, and documentation for recording classroom activities. In the first cycle, the implementation of role play increased student involvement, although some students lacked confidence and time for adequate preparation. The posttest results indicated that 70% of students had achieved the learning goals. To overcome these challenges, the second cycle included increased motivation, extended practice time, and more intensive guidance. As a result, student participation and understanding improved significantly, with 90% of students reaching mastery. Moreover, students became more confident, actively engaged, and able to convey the content effectively through their roles. The findings demonstrate that the role play method is effective in enhancing both cognitive understanding and classroom interaction. It not only supports comprehension of the Pillars of Islam but also nurtures student confidence, communication, collaboration, and enthusiasm in learning. Therefore, the role play method is recommended as an engaging and effective instructional approach for Islamic Religious Education in elementary schools.